Balmis expedition: the children who carried the smallpox vaccine to America - Reguera Teba, Antonio (Medicina Historica, 2022)
Although today very few doubt the efficacy of vaccines, when in 1796 the English doctor Edward Jenne tfler demonstrated the efficacy of his smallpox vaccine, not the entire scientific world welcomed the advance with enthusiasm. Among the most fervent defenders of the revolutionary method was the Spanish doctor Francisco Javier Balmis Berenguer from the outset. His enthusiasm led him to lead what can be considered the first humanitarian mission in history, which between 1803 and 1806 brought Jenner's vaccine to America and Asia